PENGEMBANGAN LIFE SKILLS MELALUI OLAHRAGA HOKI DALAM RANGKA POSITIVE YOUTH DEVELOPMENT (PYD) - Sely Widiyawan Ningsih, - (2022)
This study aims to analyze the improvement of life skills between adolescents who are given a life skills program and adolescents who are not given a life skills program in youth hockey sports. The population in this study were 20 people. The sample in this study used saturated sampling, which involved the entire population. The instrument used is the Life Skills Scale for Sport (LSSS) questionnaire. The data analysis of this study used normality test, homogeneity test and hypothesis testing with data processing using statistical product for social science (SPSS) 25 program. The results of this study found that the calculated T value was 50.98 > T table 2.101 then Ho was rejected and Ha was accepted, so that it can be concluded that there are differences in the improvement of life skills between adolescents who are given life skills programs and adolescents who are not given life skills programs. This confirms that the life skills program in youth hockey is very effective to implement. Thus the hypothesis is tested and can be accepted. Keywords: Life Skills. Youth Sport, Hockey, Positive Youth Development